Generalized Joint Laxity in Orthopaedic Patients: Clinical Manifestations, Radiographic Correlates, and Management. (20th March 2019) - Sacks, Hayley A.; Prabhakar, Pooja; Wessel, Lauren E.; Hettler, Jessica; Strickland, Sabrina M.; Potter, Hollis G.; Fufa, Duretti T.
Abstract : Careful history and examination may reveal a constellation of musculoskeletal conditions associated with generalized joint laxity, including shoulder instability, posterolateral rotatory instability of the elbow, wrist ganglia, thumb base pathology, hip labral pathology, and patellar and ankle instability. Subtle but highly suggestive findings associated with generalized joint laxity may be recognized on radiographs or magnetic resonance imaging that can impact the clinician's decision-making. Increasing evidence has suggested that clinical outcomes of various surgical procedures around the shoulder, hip, knee, and ankle may be impacted in patients with generalized joint laxity. Surgeons should counsel these patients accordingly to manage expectations. Patients presenting to orthopaedic specialists should be queried about symptoms and injuries in other joints to identify patients with generalized joint laxity in order to initiate early management and injury prevention protocols.